2022
DOI: 10.1088/1674-1056/ac4748
|View full text |Cite
|
Sign up to set email alerts
|

Transient electromagnetically induced transparency spectroscopy of 87Rb atoms in buffer gas

Abstract: We have studied the transient response dynamics of 87Rb atomic vapor buffered in 8 Torr Ne gas through an electromagnetically induced transparency configured in Λ-scheme. Experimentally, the temporal transmission spectra versus probe detuning by switching on and off the coupling one show complex structures. The transmitted probe light intensity drops to a minimum value when the coupling light turns off, showing a strong absorption. While at the moment of turning on the coupling light at a subsequent delayed ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…In the past ten years, Rydberg atomic microwave sensors [1][2][3] have made significant progress due to ravishing characteristics that classical radio-frequency (RF) microwave (MW) technology does not have, including self-calibration, [4] high sensitivity, [5,6] broad operation frequency. [2,[7][8][9][10] It has a wide range of applications, such as sensors for communication signals (amplitude modulated, [11][12][13] frequency modulated, [14] phase modulated signals [15][16][17] ), Rydberg microwave frequency comb spectrometer, [18] and imaging. [19] It has been theoretically demonstrated that measurement sensitivity limit of Rydberg atomic microwave sensor is −220 dBm/Hz, [20] which is far exceeding classical sensor sensitivity limit of −174 dBm/Hz (room temperature).…”
Section: Introductionmentioning
confidence: 99%
“…In the past ten years, Rydberg atomic microwave sensors [1][2][3] have made significant progress due to ravishing characteristics that classical radio-frequency (RF) microwave (MW) technology does not have, including self-calibration, [4] high sensitivity, [5,6] broad operation frequency. [2,[7][8][9][10] It has a wide range of applications, such as sensors for communication signals (amplitude modulated, [11][12][13] frequency modulated, [14] phase modulated signals [15][16][17] ), Rydberg microwave frequency comb spectrometer, [18] and imaging. [19] It has been theoretically demonstrated that measurement sensitivity limit of Rydberg atomic microwave sensor is −220 dBm/Hz, [20] which is far exceeding classical sensor sensitivity limit of −174 dBm/Hz (room temperature).…”
Section: Introductionmentioning
confidence: 99%